Scalable Data-Driven Engineering for High-Performance Computing & Financial Services - Santosh Durgam (International Journal of Intelligent Systems and Applications in Engineering, 2025)
The study discussions will touch upon enhancements to the efficiency of high-performance computing systems through the assimilation of scalable data engineering and semiconductor verification to improve data computing technological processes, especially in the financial services sector. The authors of this study explore how computerized gross working of applications like fraud detection, risk control, and algorithmic trading can be optimized through the integration of GPU hardware verification with AI-ready systems. The major results of the study include that the performance of the system increased by 25%, and the time spent on studying cases decreased as the proposals of the GPU made it possible, and the provisions of AI-driven hardware verification to conduct the verification were enhanced by 30%. Moreover, it also found data engineering pipelines to compute 95% success rates when handling real-time financial transactions, and with latency reduced to under <5ms. A combination of scaled, automated data streams has led to cost reductions of 15-20% per year, and the use of machine learning in semiconductor testing has shown that the decrease in tests could be up to 90%. The paper concludes that convergence of hardware validation and scalable data engineering is a key to devising AI-ready systems, capable of meeting the computational needs of the present financial services, enhancing reliability, scalability, and velocity. The integration is set to drive the real-time ability of decisions in the economic field to a greater extent. DOI: https://doi.org/10.17762/ijisae.v13i2s.7914